The Journal of Agricultural Science (Cambridge University Press)
This journal publishes papers concerned with the advance of Agriculture and the use of land resources throughout the world. It publishes original scientific work related to strategic and applied studies in all aspects of agricultural science and exploited species as well as reviews of scientific topics of current agricultural relevance
Keywords: Agricultural Science